2011
DOI: 10.1530/erc-10-0317
|View full text |Cite
|
Sign up to set email alerts
|

Combination of trastuzumab and letrozole after resistance to sequential trastuzumab and aromatase inhibitor monotherapies in patients with estrogen receptor-positive, HER-2-positive advanced breast cancer: a proof-of-concept trial (SAKK 23/03)

Abstract: A sequential treatment design was chosen in this trial to ensure complete resistance to singleagent non-steroidal aromatase inhibitor (AI) and trastuzumab both given as monotherapy before receiving the combination of a non-steroidal AI and trastuzumab. Key eligibility criteria included postmenopausal patients with advanced, measurable, human epidermal growth factor receptor-2 (HER-2)-positive disease (assessed by FISH, ratio (R2)), hormone receptor (HR)-positive disease, and progression on prior treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Overexpression of EGFR or HER2 generally downregulates ERα expression in experimental models [132], and HER2 overexpression is often associated with a clinically meaningful but less robust response to endocrine therapies [133]. Studies in the subgroup of ERα+/HER2+ breast cancers, comprising approximately 10% of all ERα+ breast cancers, suggest a modest potential benefit in combining endocrine therapies with inhibition of HER2 or its signaling for these patients [134136]. Whether strategies that combine EGFR and endocrine interventions will have an advantage in the chemopreventive setting also remains unclear [137].…”
Section: Growth Factors Growth Factor Receptors and Oncogenesmentioning
confidence: 99%
“…Overexpression of EGFR or HER2 generally downregulates ERα expression in experimental models [132], and HER2 overexpression is often associated with a clinically meaningful but less robust response to endocrine therapies [133]. Studies in the subgroup of ERα+/HER2+ breast cancers, comprising approximately 10% of all ERα+ breast cancers, suggest a modest potential benefit in combining endocrine therapies with inhibition of HER2 or its signaling for these patients [134136]. Whether strategies that combine EGFR and endocrine interventions will have an advantage in the chemopreventive setting also remains unclear [137].…”
Section: Growth Factors Growth Factor Receptors and Oncogenesmentioning
confidence: 99%
“…The overexpression of HER2 in luminal tumors have also been associated with increased relapse rate in patients treated with endocrine therapy, compared with HER2 negative tumours 57 . Moreover, in those patients with HER2-overexpressing tumors, the combination of endocrine and anti-HER2 therapy revealed a significant therapeutic benefit (Table 1.3) 21,35,36,58,59 , and recent evidence further suggested that complete resistance to both Anastrozole and Trastuzumab sequential monotherapies can be overcome in a proportion of patients, through the combined treatment with these compounds 60 .…”
Section: Current Therapeutic Approachesmentioning
confidence: 99%
“…Fulvestrant (to destroy the ER) plus an aromatase inhibitor is superior to either strategy alone [86] and trastuzumab reverses letrozole resistance and amplifies the sensitivity of breast cancer cells to estrogen [161]. Each of these strategies have been addressed in clinical trials [162164] recruiting patients with ER-positive tumors in late-stage breast cancer, but it will be in the adjuvant setting that most gains may occur for patient survivorship. Osborne’s group [155,165] has independently pioneered the strategy of using multiple inhibitors of the growth factor receptor family in combination with either estrogen deprivation or tamoxifen therapy and these strategies are moving into clinical trial.…”
Section: Clinical Translation Via Cell Models Of Er-positive Breast Cmentioning
confidence: 99%